The diversity and use of dwarf swamp forest vegetation in a tropical floodplain lake in West Kalimantan, Indonesia - Kurniawan, Riky; Evi Susanti; Eka Prihatinningtyas; Dian Oktaviyani; Agus Waluyo; Aiman Ibrahim; I Gusti Ayu Agung Pradnya Paramita; Muhammad Suhaemi Syawal; Pratiwi Lestari; Desy Aryani (LIMNOTEK Perairan Darat Tropis di Indonesia, 2023)
To alleviate the consequence of severe biodiversity threats, fifteen national priority lakes to be rehabilitated have been declared in Indonesia. Lake Sentarum National Park (LNSP), one of the lakes, is a distinctive floodplain lake that exhibits significant vegetation and flora diversity. One particular ecosystem type in the area is dwarf swamp forest vegetation, which displays enormous amounts of floral vegetation in that area. This study intends to uncover vegetation data in the dwarf swamp forest habitat, which currently has relatively limited data series about its diversities. The vegetation specimens were collected using a 50 x 50 m line transect. Fourteen species from ten families were collected from six observation stations. The most prevalent vegetation is C. cf. ensifolius, I. mentangis, and B. acutangula. The species diversity index (H') is 1.78 (low category), and the small lake area has a greater species variety than the river area in the LNSP area. Furthermore, we found that dwarf swamp forest vegetation is mainly used as food for Apis dorsata honey bees to produce forest honey. The findings of this study will be helpful as a fundamental reference for future monitoring, research, and conservation efforts in the park.